An exploratory study of the tourism industry in Singapore : strategic implications - Lim, Grace Mei Lan (2014)
Tourism is the world's largest single industry and its socioeconomic benefits, in terms of tourist receipts, employment and infrastructure development, are of immense importance to Singapore, which has scarce resources. This has prompted an exploratory to gain a deeper understanding of the characteristics of Singapore's tourism industry and the implications for its future.